2019
DOI: 10.4103/ijo.ijo_2143_18
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of steroid misuse in vernal keratoconjunctivitis resulting in steroid induced glaucoma and visual disability in Indian rural population: An important public health problem in pediatric age group

Abstract: Purpose:To know the pattern of presentations and management outcome of steroid induced glaucoma in vernal keratoconjunctivitis (VKC).Methods:Children of VKC using steroid with two of the following criteria were enrolled: Intraocular pressure (IOP) >21 mm Hg, glaucomatous optic disc and visual field defects. Misused topical steroids were classified in 4 groups; A- Highly potent drugs (dexamethasone, betamethasone), B- Moderate (prednisolone), C- Weak (loteprednol, fluorometholone), D- Unknown drugs. Active/cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
(24 reference statements)
1
27
0
1
Order By: Relevance
“…In our study the prevalence is around 4.16%. 5 Marcuss ang et al, in their study showed 41(28.3%) out of 145 patients developed ocular hypertension in which 8(5.5%) patients progressed to glaucoma. 5 Corticosteroid induced IOP elevation is an iatrogenic condition caused by decreased trabecular outflow, usually reversible if the steroid therapy is discontinued earlier but when unrecognised causes primary open angle glaucoma, ultimately leading to glaucomatous optic atrophy which is irreversible.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our study the prevalence is around 4.16%. 5 Marcuss ang et al, in their study showed 41(28.3%) out of 145 patients developed ocular hypertension in which 8(5.5%) patients progressed to glaucoma. 5 Corticosteroid induced IOP elevation is an iatrogenic condition caused by decreased trabecular outflow, usually reversible if the steroid therapy is discontinued earlier but when unrecognised causes primary open angle glaucoma, ultimately leading to glaucomatous optic atrophy which is irreversible.…”
Section: Discussionmentioning
confidence: 92%
“…Usually prescribed by pharmacy, general practitioners and quacks without the knowledge of its complications. 5 Vision loss resulting from cataract is reversible and relatively easy to manage but glaucoma is often recognised late leaving patients with permanent visual impairment. 6 Current therapy of ocular allergy involves elimination of the offending allergen, modulation of the immune system, and pharmacologic inhibition of the chemical mediators and rebamipide can be effective in VKC with giant papillae not responding to topical steroid.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 In addition, difficulties with drop administration technique (bottle tip contamination, failure to wash hands before eye drop instillation, and frequent hand-to-face contact during instillation) all lead to an increased risk of infections or injury. 42 Conversely, steroid eye drops can also be overused, either intentionally because they provide good symptomatic relief 45 or unintentionally because of the difficulty instilling a single drop. 44 In either case, overuse can lead to steroid-induced glaucoma and cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Low prevalence of steroid-induced glaucoma in the population would imply that it may not qualify to be a crucial public health issue to attract allocation of resources to plan preventive measures. However, a high incidence of glaucoma with insidious blindness and late presentation as in the study reported by Sen et al [10] in children using steroids would result in a significant proportion of blind years in those affected and care provider burden. There is no information of the direct economic impact of steroid-induced glaucoma and blindness in children, while childhood blindness accounted for close to USD 22.2 billion[11] cumulative loss over a lifetime in India in 1997.…”
mentioning
confidence: 99%
“…Studies[39] in the recent past have highlighted the significant role played by injudicious use of corticosteroids in children, especially vernal keratoconjunctivitis, with a considerable proportion of those with acquired childhood glaucoma to be because of steroid induced. Sen et al [10] have studied the prevalence of steroid-induced glaucoma in a large cohort of children with vernal keratoconjuctivitis. In total, 15% of the children in their study have been using topical steroids for therapy without physician prescriptions and a little more than 3% of the children had steroid-induced glaucoma.…”
mentioning
confidence: 99%